Odpowiedzialność człowieka za świat stworzony według Maksyma Wyznawcy - Kochańczyk-Bonińska, Karolina (Verbum Vitae, 2017)
Maximus the Confessor combined rich philosophical traditions with a theological heritage, but he also presented his own original vision of the role of man in the universe. A coherent cosmological and anthropological system becomes the basis for the fundamental human responsibility for the universe within the divine economy. Maxim recognizes that man is not only the microcosm, but also the mediator, between creature and Creator. Analysis of the Confessor’s works allows us to conclude that since the ultimate aim of the universe is its deification, the mission entrusted to man is to recognize this purpose and to participate in its realization.